1992
DOI: 10.1037/0735-7044.106.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Saccharin's rewarding, conditioned reinforcing, and memory-improving properties: Mediation by isomorphic or independent processes?

Abstract: Unconditioned reward and conditioned reinforcing effects may reflect an isomorphic motivational process because increased conditioned reinforcing effects were seen with increased amounts of saccharin consumed in taste and place conditioning. Reinforcing effects in place conditioning leveled off as saccharin unconditioned consumption reached maximum amounts of approximately 140 mg/rat. Posttrial consumption, but not intraperitoneal injection, of saccharin significantly enhanced conditioned place and taste prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 74 publications
(171 reference statements)
2
18
1
1
Order By: Relevance
“…The most striking difference between gp120‐tg and non‐tg mice was in their preference for the highly palatable reinforcer saccharin, with gp120‐tg mice showing greater saccharin preference and consumption compared with non‐tg mice. Saccharin is naturally rewarding to rodents due almost exclusively to its sweet taste (Stefurak & van der Kooy ). Interestingly, saccharin consumption has been shown to be a predictor of the development of drug and alcohol dependence in rats (Gosnell et al .…”
Section: Discussionmentioning
confidence: 99%
“…The most striking difference between gp120‐tg and non‐tg mice was in their preference for the highly palatable reinforcer saccharin, with gp120‐tg mice showing greater saccharin preference and consumption compared with non‐tg mice. Saccharin is naturally rewarding to rodents due almost exclusively to its sweet taste (Stefurak & van der Kooy ). Interestingly, saccharin consumption has been shown to be a predictor of the development of drug and alcohol dependence in rats (Gosnell et al .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that previous exposure to natural reward or addictive drugs can cross-sensitize animals to other addictive substances through the common reward circuits (Itzhak and Martin, 1999; Biala and Weglinska, 2004; Clark and Bernstein, 2006; Avena et al, 2008). High concentrations of saccharin, despite the aversive taste, have strong rewarding, conditioned reinforcing, and memory-improving properties (Stefurak and van der Kooy, 1992). Therefore, it is likely that a high concentration of saccharin functions as an addictive substance, sensitizing the rewarding neuronal circuits.…”
Section: Discussionmentioning
confidence: 99%
“…The solutions tested in the two-bottle consumption studies were 5% sucrose, which is palatable and nutritive, as well as 0.1% saccharin and 0.6% saline, which are also tasteful for rats but are not nutritive (Fregly and Rowland 1992; Hausmann 1933; McHugh 1979; Stefurak and van der 1992; Warwick and Weingarten 1996). Consistent with previous reports (Fregly and Rowland 1992; Hausmann 1933; Hayward et al 2006; Stewart et al 1994), under basal conditions, all three palatable fluids were preferred to water; however, sucrose, at the concentrations used, was consumed more avidly than the two other solutions.…”
Section: Discussionmentioning
confidence: 99%